2019
DOI: 10.1002/jcp.28686
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine protects against apoptosis of mesenchymal stem cells induced by high glucose

Abstract: In diabetes, the number of bone mesenchymal stem cells (MSCs) decreases and their differentiation is impaired. However, the exact mechanism is unclear. Patients with diabetes often experience sympathetic nerve injury. Norepinephrine (NE), a major mediator of the sympathetic nervous system, influences rat MSC migration in culture and in vivo. The present study aimed to investigate the effect of NE on MSCs under high glucose conditions; therefore MSCs were treated with high glucose and NE. High glucose-induced M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 63 publications
(99 reference statements)
0
23
0
Order By: Relevance
“…Then, the cells were cultured in HG (25 mmol/L) DMEM for two weeks and then harvested for further analysis. 26 Morroniside was dissolved in phosphate-buffered saline (PBS) at different concentrations (1, 10 and 100 μmol/L) for dose-dependent treatments except for the Counting Kit-8 (CCK-8) assay, where we added a group of 1000 μmol/L morroniside. When the concentration of morroniside is not specifically defined, the concentration was 100 μmol/L.…”
Section: Isolation and Culture Of Rat Bmscsmentioning
confidence: 99%
“…Then, the cells were cultured in HG (25 mmol/L) DMEM for two weeks and then harvested for further analysis. 26 Morroniside was dissolved in phosphate-buffered saline (PBS) at different concentrations (1, 10 and 100 μmol/L) for dose-dependent treatments except for the Counting Kit-8 (CCK-8) assay, where we added a group of 1000 μmol/L morroniside. When the concentration of morroniside is not specifically defined, the concentration was 100 μmol/L.…”
Section: Isolation and Culture Of Rat Bmscsmentioning
confidence: 99%
“…group (3.75±0.54) h and HG-LG group (3.83±0.51) h, F12 group (9.40±0.83) h, HG group (12.67±1 25). h. There was no signi cant difference in the 75% cell adhesion time of LG group and HG-LG group, while the difference between the other each two groups were statistically different (P<0.01).…”
mentioning
confidence: 80%
“…Studies have shown that medium with high glucose concentration within a certain range could effectively improve the proliferation ability of MSCs [23,24]. However, some studies also have shown that medium with high glucose might accelerate cell senescence and apoptosis in seveal pathways [25][26][27]. Yanan Kong et al cultured MSCs with high glucose (33 mmol/L) medium, and found that the apoptosis rate of cells remained low after culturing for 1 day, while the apoptosis rate of cells increased greatly after culturing for 5 days [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs were isolated as before [17]. Brie y, bone marrow cells were collected by ushing the femurs and tibias of 4 weeks old mice(n=10).…”
Section: Isolate and Culture Bone-marrow-derived Mscsmentioning
confidence: 99%